Competitive Advantage in Nonprofit Grant Markets: Implications of Network Embeddedness and Status. Issue 2 (3rd April 2017) - Faulk, Lewis; McGinnis Johnson, Jasmine; Lecy, Jesse D.
ABSTRACT: This article empirically addresses the effects of network embeddedness on nonprofit organizations' ability to access financial resources within competitive markets, with a focus in this analysis on the acquisition of foundation grants. We test theory on the role of organizational status in competitive markets using data from a network of nonprofits linked by foundation grants in metropolitan Atlanta during 2000 and 2005. We find that observable characteristics of nonprofits, including size, fundraising expenses, and financial health, explain success in grant markets. However, market status in previous time periods, operationalized as prior relationships with influential foundations in grant markets, additionally explains future grant awards. Our findings suggest that the status conferred through connections to important actors in a network can raise the profile of a nonprofit and increase the probability of grant success.